2022
DOI: 10.5935/0004-2749.20230037
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes and prognostic factors following 23G vitrectomy for vitreous hemorrhage in eyes with proliferative diabetic retinopathy

Abstract: The trial number is IRCT20200312046750N1 26-03-2020 and it was retrospectively registered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…While the initial VA in the two groups was comparable, the proportion of eyes with TRD and VH at presentation was significantly higher in group A. It has been demonstrated that patients who present with TRD and VH have a better visual prognosis than those who need surgery for TRD without VH (presumably with a VA decrease caused by a detached macula) [ 21 , 22 ]. Additionally, a larger number of patients in group A presented with extramacular TRD.…”
Section: Discussionmentioning
confidence: 99%
“…While the initial VA in the two groups was comparable, the proportion of eyes with TRD and VH at presentation was significantly higher in group A. It has been demonstrated that patients who present with TRD and VH have a better visual prognosis than those who need surgery for TRD without VH (presumably with a VA decrease caused by a detached macula) [ 21 , 22 ]. Additionally, a larger number of patients in group A presented with extramacular TRD.…”
Section: Discussionmentioning
confidence: 99%